The Effect of Peer Group Education on Knowledge Levels About the Dangers of Free Sex in Adolescents - Ima Sukmawati; Ayu Silpiani; Elis Noviati; Yuyun Rahayu; Heni Marliany; Rosmiati Rosmiati (Program Studi S1 Kebidanan - Fakultas Ilmu Kesehatan Universitas PGRI Adi Buana Surabaya, 2023)
According to the World Health Organization (WHO), in 2018 stated that 33 percent of Indonesian teenagers engage in promiscuous sex. The consequences of unrestricted sex include the development of venereal illnesses, STDs, and HIV/AIDS, as well as unintended pregnancy. Peer Group Education is one method for delivering accurate knowledge regarding free sex. It is considered twice as effective as other methods because the facilitator creates a more open atmosphere with a friendly approach, not patronising or judging. The goal of this study is to see how peer group education affects teenagers' understanding of the consequences of unrestricted sex. This study is pre-experimental, with a one-group pretest-posttest design and complete sampling. A questionnaire was used to collect data. The sample size was 42 people which was conducted at SMKN 1 Rancah in March 2022. The results showed that most participants had poor knowledge before the peer group discussion intervention. However, after the intervention, most participants were categorised as having good knowledge, with a mean plus minus standard deviation (SD) change before and after the intervention of 34.90 plus minus 3.37 to 47.24 plus minus 1.39. There is an effect of peer group education on the level of knowledge about the dangers of free sex in adolescents. A structured and comprehensive education programme on the various aspects of the dangers of casual sex, including physical and mental health risks, and social impacts, as well as solutions and strategies to avoid it, is needed.